Characterizing the Genetic Architecture of Parkinson's Disease in Latinos. Issue 3 (22nd July 2021) - Loesch, Douglas P.; Horimoto, Andrea R. V. R.; Heilbron, Karl; Sarihan, Elif I.; Inca‐Martinez, Miguel; Mason, Emily; Cornejo‐Olivas, Mario; Torres, Luis; Mazzetti, Pilar; Cosentino, Carlos; Sarapura‐Castro, Elison; Rivera‐Valdivia, Andrea; et al.
Abstract : Objective: This work was undertaken in order to identify Parkinson's disease (PD) risk variants in a Latino cohort, to describe the overlap in the genetic architecture of PD in Latinos compared to European‐ancestry subjects, and to increase the diversity in PD genome‐wide association (GWAS) data. Methods: We genotyped and imputed 1, 497 PD cases and controls recruited from nine clinical sites across South America. We performed a GWAS using logistic mixed models; variants with a p ‐value <1 × 10 −5 were tested in a replication cohort of 1, 234 self‐reported Latino PD cases and 439, 522 Latino controls from 23andMe, Inc. We also performed an admixture mapping analysis where local ancestry blocks were tested for association with PD status. Results: One locus, SNCA, achieved genome‐wide significance ( p ‐value <5 × 10 −8 ); rs356182 achieved genome‐wide significance in both the discovery and the replication cohorts (discovery, G allele: 1.58 OR, 95% CI 1.35–1.86, p ‐value 2.48 × 10 −8 ; 23andMe, G allele: 1.26 OR, 95% CI 1.16–1.37, p ‐value 4.55 × 10 −8 ). In our admixture mapping analysis, a locus on chromosome 14, containing the gene STXBP6, achieved significance in a joint test of ancestries and in the Native American single‐ancestry test ( p ‐value <5 × 10 −5 ). A second locus on chromosome 6, containing the gene RPS6KA2, achieved significance in the African single‐ancestry test ( p ‐value <5 × 10 −5 ). Interpretation: This study demonstrated the importance of the SNCA locus for the etiology of PD in Latinos. By leveraging the demographic history of our cohort via admixture mapping, we identified two potential PD risk loci that merit further study. ANN NEUROL 2021;90:353–365